The role of coaching identity and life purpose orientations in holistic athlete development. Issue 3 (June 2022) - Yukhymenko-Lescroart, Mariya A.; Sharma, Gitima
Life purpose plays an important role in the wellbeing of adults. The current study considered domain-general and domain-specific purpose of NCAA coaches to examine whether purpose orientation in life predicted coaching purpose related to holistic athlete development directly and indirectly through coaching identity. A cross-sectional design was used. Collegiate coaches ( N  = 380, 62.1% male) from NCAA Division I and III institutions completed questionnaires assessing purpose orientation (career-focused, others-growth, and self-growth), coaching identity (winning-centered, holistic development-centered), and coaching purpose related to athlete development (sport-specific competence, sport-general competence, confidence, connection, and character). Structural equation modeling indicated the following: Coaching purpose related to sport-specific competence was predicted directly and indirectly via winning-centered coaching identity by career-focused purpose orientation. The four dimensions of coaching purpose (sport-general competence, confidence, connection, and character) were predicted indirectly via development-centered coaching identity by others-growth purpose orientation and by career-focused purpose orientation. Others-growth purpose orientation emerged as a significant direct predictor of coaching purpose related to connection. Inconsistent mediation emerged between others-growth purpose orientation and coaching purpose related to confidence. Overall, the findings highlight that purpose orientation can predict coaching purpose and that coaching identity centered around athletes' holistic development and growth plays a salient role in explaining these relationships.